High‐throughput sequencing identifies aetiology‐dependent differences in ductular reaction in human chronic liver disease. Issue 1 (30th January 2019) - Govaere, Olivier; Cockell, Simon; Van Haele, Matthias; Wouters, Jasper; Van Delm, Wouter; Van den Eynde, Kathleen; Bianchi, Arianna; van Eijsden, Rudy; Van Steenbergen, Werner; Monbaliu, Diethard; Nevens, Frederik; Roskams, Tania
Abstract: Ductular reaction (DR) represents the activation of hepatic progenitor cells (HPCs) and has been associated with features of advanced chronic liver disease; yet it is not clear whether these cells contribute to disease progression and how the composition of their micro‐environment differs depending on the aetiology. This study aimed to identify HPC‐associated signalling pathways relevant in different chronic liver diseases using a high‐throughput sequencing approach. DR/HPCs were isolated using laser microdissection from patient samples diagnosed with HCV or primary sclerosing cholangitis (PSC), as models for hepatocellular or biliary regeneration. Key signals were validated at the protein level for a cohort of 56 patients (20 early and 36 advanced stage). In total, 330 genes were significantly differentially expressed between the HPCs in HCV and PSC. Recruitment and homing of inflammatory cells were distinctly different depending on the aetiology. HPCs in PSC were characterised by a response to oxidative stress (e.g. JUN, VNN1 ) and neutrophil‐attractant chemokines ( CXCL5, CXCL6, IL‐8 ), whereas HPCs in HCV were identified by T‐ and B‐lymphocyte infiltration. Moreover, we found that communication between HPCs and macrophages was aetiology driven. In PSC, a high frequency of CCL28‐positive macrophages was observed in the portal infiltrate, already in early disease in the absence of advanced fibrosis, while in HCV, HPCs showed a strong expression of the macrophage scavenger receptor MARCO. Interestingly, DR/HPCs in PSC showed more deposition of ECM (e.g. FN1, LAMC2, collagens) compared to HCV, where an increase of pro‐invasive genes (e.g. PDGFRA, IGF2 ) was observed. Additionally, endothelial cells in the vicinity of DR/HPCs showed differential immunopositivity (e.g. IGF2 and INHBA expression). In conclusion, our data shine light on the role of DR/HPCs in immune signalling, fibrogenesis and angiogenesis in chronic liver disease. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.